2005
DOI: 10.1111/j.1464-5491.2005.01448.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cardiovascular morbidity and mortality associated with metformin use in subjects with Type 2 diabetes

Abstract: Metformin monotherapy was associated with a lower risk of cardiovascular-related morbidity and mortality, and combination metformin and sulphonylurea therapy was associated with a reduced risk of fatal cardiovascular events, when compared with sulphonylurea monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
106
2
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(117 citation statements)
references
References 28 publications
1
106
2
7
Order By: Relevance
“…These findings are in contrast to those reported by Olsson and co-workers [7], also referred to by Tayek in his letter [1]. Although Olsson and colleagues reported that mortality was increased in diabetic patients given a combination of sulfonylurea and metformin compared with those patients given sulfonylurea alone, this study involved far fewer patients than the study by Johnson et al [6]. Moreover, Olsson et al [7] state that the observed increased mortality in the combination group may be secondary to a more aggressive type of diabetes.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…These findings are in contrast to those reported by Olsson and co-workers [7], also referred to by Tayek in his letter [1]. Although Olsson and colleagues reported that mortality was increased in diabetic patients given a combination of sulfonylurea and metformin compared with those patients given sulfonylurea alone, this study involved far fewer patients than the study by Johnson et al [6]. Moreover, Olsson et al [7] state that the observed increased mortality in the combination group may be secondary to a more aggressive type of diabetes.…”
contrasting
confidence: 55%
“…This finding is difficult to interpret as patients given higher doses of oral glucose-lowering therapies may have presented with worse glycaemia and/or more advanced type 2 diabetes, which are confounding factors. The same group of investigators demonstrated in another two studies [5,6] using the same database that, compared with sulfonylurea monotherapy, the combination of sulfonylurea and metformin is associated with a reduced risk of mortality. These findings are in contrast to those reported by Olsson and co-workers [7], also referred to by Tayek in his letter [1].…”
mentioning
confidence: 99%
“…Reduced cardiovascular risk appeared to be largely independent of glucose-lowering efficacy and attention is drawn to a substantial literature noting potentially advantageous effects of the drug on the macro-and microvasculature (Table 3) [70,71]. Interrogation of large databases that captured longterm treatment of type 2 diabetes consistently confirmed the reduced cardiovascular risk with metformin, and a 10-year follow-up of the UKPDS in 2008 showed a continued cardiovascular benefit of early use of the drug [72][73][74].…”
Section: The Ukpds and Long-term Retrospective Studiesmentioning
confidence: 96%
“…Our findings, which controlled for many potential confounding variables, found no significant increase in mortality associated with metformin used alone or in combination with sulfonylureas. Recently, studies published by Johnson and colleagues (7,20) concluded that metformin alone and in combination was associated with a reduced risk of mortality. Our sample size and duration of follow-up may have limited our ability to detect any potential beneficial effect of drug therapy on allcause mortality.…”
mentioning
confidence: 99%